Avaliaç\~ao de efeitos da Cooperaç\~ao Sul-Sul para o desenvolvimento do Brasil: Um modelo geral para projetos bilaterais com países africanos de língua portuguesa - Rafael T. Schleicher; Marília Miranda; Simone Franco (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
This document intends to contribute to the broader debate about the evaluation and quantification of South-South Cooperation, as advanced in numerous international instruments, such as the Buenos Aires Plan of Action Plus 40 (BAPA+40). The analysis revolves around four South-South Cooperation for Development (SSCD) bilateral projects with portuguese-speaking african countries, whose data was collected using standardized questionnaires and shared by the Brazilian Cooperation Agency. The data analysis revealed that creating a generalized logic model and a standardized instrument for data collection is a viable option for the Brazilian SSCD, which would eventually strengthen systematization and quantification. The direct by-products of the analysis are a generalized effects evaluation model for the Brazilian bilateral SSCD projects as well as a standardized questionnaire for systematized data collection.
Keywords: C18; F54; I23; I26; 330; South-South cooperation; project evaluation; impact evaluation; capacity development; international technical cooperation; brazilian international cooperation